2008
DOI: 10.1007/s12111-008-9054-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Discrimination: Multiple Measures and the Intersections of Race and Gender

Abstract: The purpose of this paper is to investigate the degree to which adults in four racial/gender categories perceive that they experience discrimination. Using the 1995-1996 National Survey of Midlife Development in the United States (MIDUS), the author employs logistic regression to compare the likelihood of perceiving specific types of discrimination for black men, black women, white men, and white women. Results indicate that variations in perceived discrimination occur across the racial/ gender categories. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Surprisingly, we found little variation in experiences of discrimination among black adults by socioeconomic status, gender, and neighborhood racial composition, likely because of the high proportion of black adults who reported experiencing discrimination across domains. Discrimination experiences varied by domain, consistent with prior research showing that reporting discrimination varies by both demographic characteristics and the type of discriminatory treatment tested . In addition, living in a predominantly black neighborhood was not predictive of discrimination in any domains.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Surprisingly, we found little variation in experiences of discrimination among black adults by socioeconomic status, gender, and neighborhood racial composition, likely because of the high proportion of black adults who reported experiencing discrimination across domains. Discrimination experiences varied by domain, consistent with prior research showing that reporting discrimination varies by both demographic characteristics and the type of discriminatory treatment tested . In addition, living in a predominantly black neighborhood was not predictive of discrimination in any domains.…”
Section: Discussionsupporting
confidence: 82%
“…Discrimination experiences varied by domain, consistent with prior research showing that reporting discrimination varies by both demographic characteristics and the type of discriminatory treatment tested. 28 In addition, living in a predominantly black neighborhood was not predictive of discrimination in any domains. This is inconsistent with prior research using census data which found that among blacks, living in a neighborhood with a higher percentage of blacks was associated with lower levels of discrimination.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For instance, an African American woman who experiences discrimination from a White male may be more likely to attribute a discriminatory act as being a result of her race and gender than if she experiences the same discriminatory act from other Black males or White women. African American men also may experience gendered types of discrimination in the form of more violent forms of discrimination than Black women (Rodriguez, 2008). Thus, future studies would be wise to explore the ways in which different experiences with discrimination, as a function of gender, may influence gender differences in affective responses to discrimination.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%